2021
DOI: 10.1016/s1872-2067(20)63589-6
|View full text |Cite
|
Sign up to set email alerts
|

Metal-doped Mo2C (metal = Fe, Co, Ni, Cu) as catalysts on TiO2 for photocatalytic hydrogen evolution in neutral solution

Abstract: The neutral hydrogen evolution reaction (HER) is vital in the chemical industry, and its efficiency depends on the interior character of the catalyst. Herein, work function (WF) engineering is introduced via 3d metal (Fe, Co, Ni, and Cu) doping for modulating the Fermi energy level of Mo2C. The defective energy level facilitates the free water molecule adsorption and, subsequently, promotes the neutral HER efficiency. Specifically, at a current density of 10 mA/cm 2 , Cu-Mo2C exhibits the best HER performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…22,30 The photocatalytic activity of Mo2C/TiO2 has been, however, rarely reported in the literature. 25,[31][32][33] Furthermore, an efficient system for the photocatalytic transformation of CO2 to CH3OH may not only take into account the photoactive material but the photoreactor design, trying always to effectively harness light irradiation, optimising exposure of active sites and minimizing mass transfer constraints. In this regard, the use of optofluidic microreactors may bring several advantages in the photocatalytic reduction of CO2, including large surface-area-to-volume ratio, uniform light distribution, enhanced mass transfer and fine flow control, 34 in contrast to common slurry batch-type reactors that have been demonstrated to be inefficient to induce the challenging reaction to form CH3OH, 35 due to a low surface-area-to-volume ratio because of particle agglomeration, and the required separation of the photocatalyst material from obtained products.…”
Section: Introductionmentioning
confidence: 99%
“…22,30 The photocatalytic activity of Mo2C/TiO2 has been, however, rarely reported in the literature. 25,[31][32][33] Furthermore, an efficient system for the photocatalytic transformation of CO2 to CH3OH may not only take into account the photoactive material but the photoreactor design, trying always to effectively harness light irradiation, optimising exposure of active sites and minimizing mass transfer constraints. In this regard, the use of optofluidic microreactors may bring several advantages in the photocatalytic reduction of CO2, including large surface-area-to-volume ratio, uniform light distribution, enhanced mass transfer and fine flow control, 34 in contrast to common slurry batch-type reactors that have been demonstrated to be inefficient to induce the challenging reaction to form CH3OH, 35 due to a low surface-area-to-volume ratio because of particle agglomeration, and the required separation of the photocatalyst material from obtained products.…”
Section: Introductionmentioning
confidence: 99%
“…This allows the injection of photogenerated electrons from the conduction band of the semiconductor into the metal. 29 Up to now few studies on the use of non-noble metals as cocatalysts have been reported [30][31][32][33] To analyse the photocatalytic behaviour of the prepared M/TiO 2 photocatalysts (M= Fe, Co, Ni, Cu, Zn) under both visible and UV light irradiation, TiO 2 was loaded with 2 wt% of selected transition metals. Hydrogen production profiles for TiO 2 impregnated catalysts are shown in Fig.…”
Section: Articlementioning
confidence: 99%
“…The enlarged XRD patterns ( Figure 1B) show that with the increase of the nickel content, the diffraction peak at 2θ of 39.5 • gradually shifts to higher angles. It indicates that Ni 2+ cations with smaller ionic radius than Mo 2+ cations are doped into the molybdenum carbide lattice, which makes the crystal plane spacing smaller [51]. Compared with the MC catalyst, the diffraction peak intensity of the β-Mo 2 C phase of the MC-Ni-X catalysts increases sharply.…”
Section: Introductionmentioning
confidence: 99%